Moving beyond skills acquisition: a multiple case study of situated learning in a league for children with disabilities - Rossing, Niels N.; Agergaard, Sine; Skrubbeltrang, Lotte S. (Frontiers in Sports and Active Living, 2023)
In the last few decades, there has been a movement from individualistic and mechanistic notions of learning to approaches that turn attention to the significance of the context of learning. While these approaches have been utilized to point out the significance of the environment for skill acquisition, they have primarily been oriented towards performance-oriented milieus. Inspired by the theory of situated learning in “communities of practice” (CoP), the aim of the study is to analyze learning processes among members (participants, coaches, parents, etc.) of a diverse sporting community. The article is based on a multiple-case study of a Danish handball community named Lykkeliga (Happy League) that within a few years has attracted more than a thousand children with a remarkable diverse range of age, gender, diagnosis, and disabilities. The data collection included participant observation of training and tournament situations in two clubs over a 3-month period, along with informal interviews. The thematic analysis reveals a range of legitimate ways of participating for members of Happy League clubs, including sitting on the bench and even dating during practice. In sum, our case study sheds light on how situated learning in sporting communities may be directed towards inclusion and expansive understanding of what it means to be a sport participant.